Programmable Automatic Lighting Control System - Benedictus Herry Suharto (Media Aplikom, 2010)
The aim of this research is to design and implement a programmable automatic lighting control system. The system consists of microcontroller hardware that handle lighting to turn on or turn off based on schedule. The schedule made by software application on personal computer (PC). RTC (Real-Time Clock) was used to establish timing in real time world, in order to compare with time data has been programed. In addition, USB (unversal Serial Bus) was used to establish communication between PC and the device, in order to program the schedule data in the device, so the lighting turn on or turn off schedule that runs can be customized by user. The result of the research showed that the schedule in the device, as well as in the PC, was running well, leading us to the conclusion that the programmable automatic lighting control system can be used in real life.